2021
DOI: 10.4103/ams.ams_312_20
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral condylar fracture with review of treatment modalities in 30 cases - An evaluative study

Abstract: Introduction: The treatment of subcondylar mandible fractures is a topic of debate and can be variable even though these fractures are commonly seen. The present study aimed at evaluation of various treatment modalities for unilateral condylar fracture in adults. Materials and Methods: Thirty patients with unilateral condylar fractures between the age of 18 and 60 years were evaluated. Treatment protocol included closed reduction for 15 patients and open reduction for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Facial expression weakness occurs in patients treated via this approach, which may be due to trauma during retraction rather than nerve damage. 13,19 In our study none of the patient observed with facial nerve palsy in open reduction group.…”
Section: Stability Of Fractured Fragment and Osteosynthesis Devicementioning
confidence: 45%
See 4 more Smart Citations
“…Facial expression weakness occurs in patients treated via this approach, which may be due to trauma during retraction rather than nerve damage. 13,19 In our study none of the patient observed with facial nerve palsy in open reduction group.…”
Section: Stability Of Fractured Fragment and Osteosynthesis Devicementioning
confidence: 45%
“…The conservative treatment is described as safe, non-invasive, easy, and low cost, but they have also reported many complications including poor oral hygiene, gingivitis, facial deformity, TMJ dysfunction, and even TMJ ankylosis. [13][14][15][16] Surgical treatment also has disadvantages such as its high cost, intraoperative hemorrhage, facial nerve injury, and other surgical complications along with post-operative scar formation. 13 The literature on condylar fractures has reported good outcomes for both open and closed treatment methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations